1994
DOI: 10.1098/rspb.1994.0043
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of the nacreous layer in mollusc shells

Abstract: We present atomic force microscopy (afm) observations of the aragonite tablets of mature nacre in two types of mollusc, a bivalve ( A t r i n as p.) and a gastropod ( rufescens). By imaging in liquids it was possible to dissolve away the nacre layer by layer to reveal both the structure of a single tablet and its relation to vertically adjacent tablets. Atrina tablets (inner face) had a concave appearance; the central depression was surrounded by elongate rings that mimicked the orientation and aspect ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Aragonites can be aggregated to form aragonite tablets (the size is about 0.4 ∼ 2 μm, the diameter is about 3 ∼ 10 μm), and aragonite microlayers in the next. During a long period of time, the aragonite tablets had been believed to be directional arrangement and their C-crystal axis was only vertical to the stratification plane of the nacres [10]. Namely, the crystalline orientation of aragonite tablets is unique because they were crystallized along with the crystalline plane nets which were matching with the formation periods of the organic matters.…”
Section: Introductionmentioning
confidence: 94%
“…Aragonites can be aggregated to form aragonite tablets (the size is about 0.4 ∼ 2 μm, the diameter is about 3 ∼ 10 μm), and aragonite microlayers in the next. During a long period of time, the aragonite tablets had been believed to be directional arrangement and their C-crystal axis was only vertical to the stratification plane of the nacres [10]. Namely, the crystalline orientation of aragonite tablets is unique because they were crystallized along with the crystalline plane nets which were matching with the formation periods of the organic matters.…”
Section: Introductionmentioning
confidence: 94%
“…The direction of a crystal on a new layer is determined by that of the crystal of the previous layer onto which it begins to grow. In this way, we reproduce the effect of epitaxial growth, which is well established in bivalve and gastropod nacre (Manne et al 1994;Schäffer et al 1997). Finally, the program also provides the histogram of angle frequency at intervals of 108 and the mean angle between the b-axis and the growth direction (alignment of b-axis).…”
Section: (B) Competition Between Tabletsmentioning
confidence: 99%
“…In Gastropoda, nacre crystals stack in towers that finally coalesce by lateral growth (Wise 1970;Nakahara 1983Nakahara , 1991. Crystals of a same tower have their crystallographic axes co-oriented, with the c-axis along the stacking axis (Manne et al 1994). Crystals in different towers have their c-axes aligned but the a-and b-axes have an azimuthal disorder (turbostratic disposition ;Schmidt 1923;Wada 1961;Wise 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the mineral tablets apparently is determined by the matrix sheets (22), while their interdigitation is controlled, in part, by the stochastic location of nanopores in the stencillike sheets through which the crystals grow from one layer to the next (32,(35)(36)(37)(38). Electron microscopy, x-ray, and electron diffraction have shown that each sheet consists of a chitin-like core sandwiched between two layers of protein (12, 28 -30).…”
mentioning
confidence: 99%